AMTSAL AL-QUR’AN DALAM PERSPEKTIF ULUMUL QUR’AN: TELAAH DEFINISI, MACAM, DAN SIGHAT RETORIKNYA - Rachma Febriyanti; Nurul Fitrah Ilham; Halimah Basri; Syamsul Qamar (LPPM STAI Muhammadiyah Probolinggo, 2025)
Amtsal al-Qur’an refers to the rhetorical style of parables employed in the Qur’an to convey divine messages through concrete analogies that are easily understood by humans. This article aims to examine the role of amtsal al-Qur’an from the perspective of Ulumul Qur’an by exploring its definitions, classifications, and rhetorical forms (sighat). This study applies a library research method with a descriptive-analytical approach by collecting data from classical and contemporary tafsir literature as well as relevant scholarly articles. The findings show that amtsal al-Qur’an is not merely a figurative language style but also serves as an educational, rhetorical, and moral-reflective tool that grounds abstract values into tangible illustrations. Based on analysis, amtsal is classified into musharrahah, kaminah, and mursalah, while its sighat include patterns of tashbīh, majāz, and isti‘ārah. A deeper understanding of amtsal can enrich the interpretation of Qur’anic verses and strengthening contextual approaches in dakwah and value-based education. This finding is expectedly to serve as a reference for developing Ulumul Qur’an studies, especially related to tadabbur methods, dakwah, and the reinforcement of Islamic education.